Narcoterrorism dan Perdagangan Senjata Ilegal sebagai Penghubung Jaringan Terorisme Internasional - Karjaya, Lalu Putrwandi; Sood, Mohammad; Safitri, Purnami (Nation State: Journal of International Studies, 2018)
The international terrorism usually has intercourse with the illegal trade to available funds them that group can survive. Various terrorist network generally has a very different ways with the others, so it was hard to figure relation between one and the other. Nevertheless, in a manner funding had then we can see how a terrorist network was in a continent can be connected with terrorists in other continents through this funding. Terrorist financing itself obtained from illegal trade like as drug trafficking and illegal weapons. Drug trafficking by terrorists is then called narcoterrorism where business assisted by user in the world. The user uses the links between terrorist networks on the continents.